1984
DOI: 10.1159/000153485
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of &alpha;<sub>1</sub>-Antitrypsin Variants in a US White Population

Abstract: A white population from the State of Minnesota of primarily German and Scandinavian heritage was subtyped for α1-antitrypsin variants using isoelectric focusing. The frequencies of the genes PPM1 (0.724), PI*M2 (0.137) and PI*M3 (0.095) were consistent with those for white populations documented in the literature from Northern Europe. Other genes identified in the study were PI*F, PPI, PPP, PPS and PPZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0
2

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 5 publications
5
22
0
2
Order By: Relevance
“…The observed gene frequencies of the M alleles in Sweden were similar to those given for other Caucasian populations [9,10], and the frequencies of the alleles Z and S to those found in Scandinavia [11], A population study from northern Sweden [12] showed lower frequencies of the alleles Z and S than in this material.…”
Section: Resultssupporting
confidence: 88%
“…The observed gene frequencies of the M alleles in Sweden were similar to those given for other Caucasian populations [9,10], and the frequencies of the alleles Z and S to those found in Scandinavia [11], A population study from northern Sweden [12] showed lower frequencies of the alleles Z and S than in this material.…”
Section: Resultssupporting
confidence: 88%
“…Table III pres ents our results com pared with the Pi phenotype distributions reported for other European populations, a United States' white and a Japanese population sample. The frequencies of the comm on genes were com parable to the ones found in other population o f Caucasian origin [Klasen et al, 1977;W eidinger et al, 1982;Böhme et al, 1983;Dykes et al, 1984;Yua s a e ta l., 1984;Thym ann, 1986]. There are only minimal regional differences of allele frequencies in Europe.…”
Section: Resultssupporting
confidence: 48%
“…identified (Cox, 1978;Morse, 1978;Kuhnl & Spielmann, 1979;Buffone et al, 1983;Dykes et al, 1984). The association between a,AT and HCC is complex and intriguing, and may reflect both the pathophysiological role of a,AT (Eriksson, 1985;Garver et al, 1986) and its production by the liver (Glasgow et al, 1982).…”
Section: Methodsmentioning
confidence: 99%